A implementação das linhas de cuidado na saúde pública brasileira: o caso da Unidade de Saúde Escola da UFSCar - Carrijo, Elisângela Rodrigues (2013)
Accordingly to the preamble of World Health Organition (WHO), whose constitution focuses on the enjoyment of the highest attainable standard of health [which] is one of the fundamental rights of every human being without distinction of race, religion, political belief, economic or social condition , and since health has got intersectoral dimensions that are required for healthcare, we ve gathered on this paper the main challenges related to the adoption of a public health policy. From the complexity of intersectoral models to the broadening of goals, this paper rescues the building-up of the concept of health s integrality in our country. To begin with, in order to develop the survey, we will be based on Brazil s constitution of 1988; on the conception of SUS, which stands for our health services system and, at last, on the affirmation of our health system accordingly to WHO proposals. It will be also necessary to go through the social-sanitary speech in seek of the broadening of the meaning of integrality and also of multidisciplinary organicity, the latter being of recent origin. Both concepts were born in mind at the time SUS qualifying project was being made, in 2007, accordingly to Main Line Health foundations. Since the establishment of Main Line Health aims to fulfil the requirements of integrality, we attempt to identify how our public health services system has updated its concept. So as to study the implementation Main Line Health at USE-UFSCar, we have chosen to use a qualitative method because it makes easier to understand the foundations of Main Line Health implementation. Afterwards, the method applied will also help us discuss, based on different theories concerning to public policies and on recent conclusions about the same situation in Québec, Canada. To sum up, this survey focuses on the parallelism between both multidisciplinary dynamics and also on the evaluation of Brazilian health services users and québècoise efforts for public health so as to check in which ways principle of integrality has been updated since the time the Ottawa Charter for Health Promotion was published, in 1986, and Brazilian Constitution was ratified, in 1988, up to more recent days for instance, when Main Line Health was adopted by SUS, in 2007.